2002
DOI: 10.1007/bf02492900
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of a ferrocene-bonded silica phase for reversed-phase high-performance liquid chromatography

Abstract: Key WardsColumn liquid chromatography Ferrocene-bonded silica stationary phase re-re Interactions Hydrophobic interactions SummaryThe preparation, characterization, and potential liquid chromatographic applications of a ferrocene-bonded silica stationary phase are presented. The phase was prepared by covalent bonding of ferrocene-derivatized aminosilane to silica gel then end-capping with trimethylchlorosilane. Use of the new stationary phase enabled good separations of alkylbenzenes, halobenzenes, polycyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…This indicates that the rt-rt interaction between the solutes and the stationary phase is significant. This result is agreed with our previous study [11].…”
Section: The R Coeff Icier#supporting
confidence: 96%
See 1 more Smart Citation
“…This indicates that the rt-rt interaction between the solutes and the stationary phase is significant. This result is agreed with our previous study [11].…”
Section: The R Coeff Icier#supporting
confidence: 96%
“…Fc-SiO2 was ferrocene-bonded phase based on Kromasil silica (,pore size= 100A) [11]. C1~-sio2 was Hypersil C1~ (Phenomenex; pore size = 120A ).…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…Since Delville [23][24] and Zuo [25][26] reported the application of ferrocene as the stationary phase, it has attracted extensive attention in liquid chromatography [27] due to its varieties of separation mechanisms, including hydrophobic, hydrogen bonding, π-π, dipole-dipole and charge-transfer interactions. Complexing properties of ferrocene receptors depend mainly on the type and arrangement of binding site.…”
Section: Introductionmentioning
confidence: 99%
“…The grafting on silica gel of electron acceptor molecules bearing transition metal metallocenes [1][2][3][4][5] is another investigated field of research [6][7]. In recent years, the ferrocene-bonded stationary phase has attracted considerable attention in liquid chromatography due to its varieties of separation mechanisms, including hydrophobic, hydrogen bonding, π-π, dipole-dipole and charge-transfer interactions [8][9][10][11][12]. Complexing properties of ferrocene receptors depend mainly on the type and arrangement of binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Delville group [8][9] and Zuo group [10][11] demonstrated that the stationary-phase, bonded with covalently linking ferrocene of so-called "organometallic/inorganic" hybrid materials, exhibited high selectivity towards the separation of alkylbenzenes, halobenzenes, PAHs and aniline derivatives under normal-phase (NP) or reversed-phase (RP) conditions.…”
Section: Introductionmentioning
confidence: 99%